Production of Platelet-Activating Factor by Porcine Brain Microvascular Endothelial Cells in Culture - Satoh, Kei; Yoshida, Hidemi; Imalzumi, Tada-Atsu; Koyama, Masayuki; Takamatsu, Shigeru (Thrombosis and Haemostasis, 1995)
Endothelial cells produce platelet-activating factor (PAF), which is the key process in the interactions between the vascular wall and blood cells. To examine the production of PAF in brain microvasculature we have cultured brain endothelial cells and performed a comparative study with aortic endothelial cells. Fresh porcine brain was homogenized, and microvascular endothelial cells were separated by enzyme digestion. The cells were cultured in medium containing epidermal growth factor and bovine brain extract. Endothelial cells from the aorta of the same animal were cultured in a similar manner. Production of PAF was assessed by ǀ3Hǀacetate incorporation into phospholipids or by radioimmunoassay. Prostacyclin was measured by radioimmunoassay of 6-ketoprostaglandin F1α. The cells produced 1760 ± 403 and 2892 ± 347 dpm/106 cells (n = 4) of PAF when stimulated with brady- kinin and calcium ionophore A23187, each at 1 μM, respectively. Aortic endothelial cells produced 3911 ± 2006 and 8052 ± 2270 dpm/106 cells (n = 4), respectively, and these values were significantly higher than those in brain endothelial cells (p<0.01, U-test). Prostacyclin production was also higher in aortic cells as compared to brain microvascular endothelial cells. In aortic endothelial cells both Ca ionophore A23187 and bradykinin significantly stimulated PMN adherence whereas in brain microvascular cells only Ca ionophore enhanced the adherence. Brain microvascular endothelial cells produce smaller amount of PAF and prostacyclin as compared to aortic endothelial cells, and this fact may imply that the functional integrity of the brain microvascular endothelium is maintained at a low level.